Vancomycin modifies the expression of the agr system in multidrug-resistant Staphylococcus aureus clinical isolates - Cázares-Domínguez, Vicenta; Ochoa, Sara A.; Cruz-Córdova, Ariadnna; Rodea, Gerardo E.; Escalona, Gerardo; Olivares, Alma L.; Olivares-Trejo, José de Jesús; Velázquez-Guadarrama, Norma; Xicohtencatl-Cortes, Juan (Frontiers in Microbiology, 2015)
Staphylococcus aureus is an opportunistic pathogen that colonizes human hosts and causes a wide variety of diseases. Two interacting regulatory systems called agr (accessory gene regulator) and sar (staphylococcal accessory regulator) are involved in the regulation of virulence factors. The aim of this study was to evaluate the effect of vancomycin on hld and spa gene expression during the exponential and post-exponential growth phases in multidrug resistant (MDR) S. aureus. Methods. Antibiotic susceptibility was evaluated by the standard microdilution method. The phylogenetic profile was obtained by pulsed-field gel electrophoresis. Polymorphisms of agr and SCCmec were analyzed by multiplex polymerase chain reaction. The expression levels of hld and spa were analyzed by reverse transcription-PCR. An enzyme-linked immunosorbent assay assay was performed to detect protein A, and biofilm formation was analyzed via crystal violet staining. Results. In total, 60.60% (20/33) of S. aureus clinical isolates were MDR. Half (10/20) of the MDR S. aureus isolates were distributed in subcluster 10, with > 90% similarity among them. In the isolates of this subcluster, a high prevalence (100%) for the agrII and the cassette SCCmec II polymorphisms was found. Our data showed significant increases in hld expression during the post-exponential phase in the presence and absence of vancomycin. Significant increases in spa expression, protein A production and biofilm formation were observed during the post-exponential phase when the MDR S. aureus isolates were challenged with vancomycin. Conclusion. The polymorphism agrII, which is associated with nosocomial isolates, was the most prevalent polymorphism in MDR S. aureus. Additionally, under our study conditions, vancomycin modified hld and spa expression in these clinical isolates. Therefore, vancomycin may regulate alternative systems that jointly participate in the regulation of these virulence factors.